2003
DOI: 10.1182/blood-2002-09-2839
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of osteoprotegerin production is responsible for osteosclerosis in mice overexpressing TPO

Abstract: Myelofibrosis and osteosclerosis are prominent features arising in mice overexpressing thrombopoietin (TPO). The pivotal role of transforming growth factor ␤1 (TGF-␤1) in the pathogenesis of myelofibrosis has been documented, but the mechanisms mediating osteosclerosis remain unclear. Here, we used mice deficient in osteoprotegerin (OPG), a secreted inhibitor of bone resorption, to determine whether osteosclerosis occurs through a deregulation of osteoclastogenesis. Marrow cells from opg-deficient mice (opg ؊/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 55 publications
(66 reference statements)
2
64
1
Order By: Relevance
“…Although the over-expression of TPO in bone marrow cells of mice was known to result in OS as well as myelofibrosis [7], it was reported that OS had not occurred by the over-expression of TPO in OPG-deficient mice [13]. This conclusion was based not on clinical examination but an in vivo study; however, it may suggest an unspecific role of OPG in the development of OS.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Although the over-expression of TPO in bone marrow cells of mice was known to result in OS as well as myelofibrosis [7], it was reported that OS had not occurred by the over-expression of TPO in OPG-deficient mice [13]. This conclusion was based not on clinical examination but an in vivo study; however, it may suggest an unspecific role of OPG in the development of OS.…”
Section: Discussioncontrasting
confidence: 40%
“…Focusing on primary myelofibrosis, which frequently causes OS at the terminal stage, OPG was also suspected as an etiological factor of OS [13]. Although the over-expression of TPO in bone marrow cells of mice was known to result in OS as well as myelofibrosis [7], it was reported that OS had not occurred by the over-expression of TPO in OPG-deficient mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hormones such as PTH [10] and glucocorticoids [11,12] have been reported to decrease OPG concentrations while anabolic agents such as estrogens, transforming growth factor β, related bone morphogenic factor and thrombopoietin [13][14][15][16] have been shown to enhance the OPG production in the osteoblastic and bone stromal cells. Recent studies [17][18][19] have described a bimodal pattern for the variation along the 24-h scale of circulating PTH, with a major peak during the night and a secondary peak in the late afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoprotegerin is an important inhibitor of oseoclastogenesis and animals engineered to overexpress OPG develop osteopetrosis (28). Thrombopoietin up-regulates OPG expression in animal models and therefore can explain the osteosclerosis seen in this disease (29). MMM is associated with significant new vessel formation (13).…”
Section: Fibrogenic Angiogenic and Osteogenic Cytokines In MMMmentioning
confidence: 99%